Episodes. The third season [videorecording (DVD)] - LeBlanc, Matt; Mangan, Stephen; Greig, Tamsin, 1967-; Pankow, John (Paramount Pictures, 2015)
Season three picks up with Sean and Beverly, the English couple whose hit U.K. sitcom is remade for U.S. audiences and corrupted beyond recognition, back together but they soon discover that it's not so easy to heal old wounds. Things get no easier for Matt this year as his career and ego continue to be pummeled.